The EU’s new Arctic Communication:not-so-integrated, not-so-disappointing? - Stepien, Adam; Raspotnik, Andreas (Lapin yliopisto, Arktinen keskus, 2016)
On 27 April 2016, Federica Mogherini (the High Representative of the Union for Foreign Affairs and Security Policy) and Karmenu Vella (Commissioner for Environment, Maritime Affairs and Fisheries) presented the third take – following the earlier statements from 2008 and 2012 (European Commission 2008; 2012) – on the EU-Arctic nexus. The new Joint Communication is titled “An integrated European Union policy for the Arctic”. The new policy statement was requested by the Council of the European Union in 2014 and was preceded – for the first time – by a consultation process. The document provides a broad overview of various aspects of EU presence in the Arctic region. It proposes also a few – albeit not particularly many – ideas for future actions. The document does so within three “priority areas”: • Climate Change and Safeguarding the Arctic Environment; • Sustainable Development in and around the Arctic; • International Cooperation on Arctic Issues. In this ArCticle – the first of the new Arctic Centre series – we provide our perspective on a few elements that are novel and particularly interesting. The Communication proclaims itself to be a proposal for an “integrated EU Arctic policy”. We therefore discuss what an “integrated policy” could mean in the EU context and ask whether it is possible to “integrate” the diverse fields of EU-Arctic affairs. Further, we turn to the aspects that point to an on-going change in the EU’s approach to the Arctic: an increased focus on the development of the European Arctic, as well as the proposed coordination of the EU Arcticrelated funding, which also entails enhanced stakeholder engagement. Finally, we discuss the external dimension of the EU’s Arctic policy and its location in the broader circumpolar setting of Arctic cooperation and the Union’s upcoming Global Strategy.